Study protocol for a randomized controlled trial of a child and parent mindfulness intervention for pediatric venipuncture - Rachel L. Moline; Christine Chambers; C. Meghan McMurtry (Wiley, 2021)
Abstract Children commonly undergo painful needle procedures. Unmanaged procedural pain can have short‐ and long‐term consequences, including longer procedure times, greater distress at future procedures, and vaccine hesitancy. While parent behaviors are one of the strongest predictors of children's response to acute pain, pediatric procedural pain management interventions focus almost exclusively on the child. Further, existing parent‐involved pediatric pain management interventions typically fail to improve child self‐reported pain during painful procedures. The current protocol offers the first randomized controlled trial involving a mindfulness intervention for pediatric acute pain that includes children and their parents. This study aims to conduct a single‐site, two‐arm, parallel‐group RCT to examine the effects of a mindfulness intervention for parents and children before child venipuncture compared to a control group on primary (child self‐report of pain and fear), secondary (parent self‐report and child report of parent distress), and tertiary outcomes (parent report of child pain and fear). Parent‐child dyads (n = 150) will be recruited from the McMaster Children's Hospital outpatient blood laboratory. Dyads will be randomly assigned to either a mindfulness group guided through a mindfulness intervention or control group guided through an unfocused attention task. Parents will accompany their child for their venipuncture. Postvenipuncture measures will be collected (eg, child pain‐related outcomes as reported by parents and children). The first enrollment occurred in October 2019. We offer a novel intervention that aims to facilitate both parent and child coping during child venipuncture.